Agricultural growth, poverty, and nutrition linkages in Malawi - Pauw, Karl; Ecker, Olivier; Mazunda, John (International Food Policy Research Institute, 2011)
While economic growth is generally acknowledged as a necessary precondition for reducing poverty, relatively little is known about how growth and nutrition are related. Therefore, questions persist regarding how to leverage economic policies so that they have a larger impact on nutrition. In recent years the Malawian government allocated a large share of its resources to the Farm Input Subsidy Program (FISP). Subsidized fertilizer and seed mainly for maize production led to rapid GDP growth during 2005-2010. It is obvious that an abundant supply of the calorie-laden staple maize is good for reducing calorie deficiency; however, it is less clear how FISP has affected micronutrient deficiencies, which are high in Malawi. This brief explores diverse poverty and nutritional outcomes of recent maize-led growth in Malawi and considers outcomes under two plausible future growth scenarios.